IK Notes Survey Results - Reuger, Claudia (World Bank, Washington, DC, 2012)
In early 2006, the program asked for feedback on the IK Notes series (see 36060) and to assess whether they had made contributions to reader's work. The focus of the survey was on readers' perceptions of the role of indigenous knowledge in development and the World Bank's work in terms of integrating indigenous knowledge and practices into World Bank-supported programs and projects. This report is based on responses to both the web-based and the paper survey; with 213 responses (144 to the web-based and 69 to the paper-based questionnaire).